Marché de Rocinha, Rio de Janeiro (RJ) : Azevedo Arquitetos Associados (AAA) (2005)
Azevedo, Rodrigo
Castello Branco, Ricardo
Río de Janeiro
Brasil
arquitectura comercial
mercados
estructuras tensadas